SDM BERKUALITAS UNTUK MENINGKATKAN PEMBANGUNAN BERKELANJUTAN DI MASYARAKAT - Priehadi Dhasa Eka; Angga Juanda; Gunarda Gunarda; Anisa Putri Radiyana; Erlangga Restu Yudistira; Moh. Restu Sidiq (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The community service program, themed "Quality Human Resources to Improve Sustainable Development in the Community," aims to improve the capacity of human resources (HR) to support the achievement of sustainable development goals. This program is designed to provide training, supplies, and education to the community regarding the importance of skilled and educated HR in implementing the principles of sustainable development. In its implementation, this program focuses on improving community knowledge and skills in managing natural resources wisely and implementing environmentally friendly technologies. Various trainings are provided to develop sectors that have the potential to support sustainability, such as sustainable agriculture, renewable energy management, waste management, and water and soil conservation. By introducing these concepts, it is hoped that the community will understand the importance of maintaining ecosystem balance and managing natural resources without damaging the environment. In addition, this program also focuses on developing local leadership, by providing managerial and leadership skills training to community members. This aims to enable them to become agents of change capable of implementing sustainable development ideas at the local level. The training also covers work ethics, social skills, and organizational management, which will help them manage sustainable development projects more effectively. With an integrated, community-based approach, this community service program is expected to produce human resources who are not only skilled and qualified but also able to play an active role in creating a better environment and a more independent society. Through human resource empowerment, it is hoped that sustainable development can be achieved, which will positively impact the well-being of society as a whole.